Interrelationships among individual and family factors, peer relationships, acculturation and well-being of Iranian adolescents in Malaysia - Sheibani, Shahnaz (2019)
Teenage Years are vital years in the human development. According to the latest Iranian Statistics Centre report, in 2016, Iran is one of the youngest countries in the world with about 20.5 million adolescents (26%) (Parsa, 2016). In recent years, one of the critical issues in Iran is the migration of Iranian adolescents (with or without their families) to other countries. In current decades, migration of Iranian to Malaysia increased. Concerning the Iranian population in Malaysia, the academic literature relevant to the psychological outcomes for such migration are limited and, in most cases, focused solely on the adults. Hence, it is worthwhile to study the positive well- being of Iranian adolescents to support them in developing the necessary social and emotional competencies for a better transition to adulthood.